1974
DOI: 10.1038/hdy.1974.85
|View full text |Cite
|
Sign up to set email alerts
|

Supernumerary chromosomes and chiasma distribution in Triticum speltoides

Abstract: SUMMARYSupernumerary (B) chromosomes were found in two Out of three population samples of Triticum .cpeltoides from Turkey and further samples were studied from two Israeli populations previously reported to consist of a high frequency of B-carriers (Simchen et al., 1971). In the two Israeli populations, plants with B chromosomes have a lower frequency of terminal chiasmata and a higher frequency of interstitial chiasmata. This effect is proportional to the number of B chromosomes per plant, which varies in on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…Increases in mean cell chiasma frequency generally result in chiasmata being formed in these interstitial regions with concommitant breakup of supergene complexes normally inherited as units. Again this situation is similar to that described in Lolium and Festuca by Rees and Dale (1974), in wheat by Zarchi et a!., (1972Zarchi et a!., ( , 1974 and in rye by Jones (1974).…”
Section: Resultssupporting
confidence: 71%
“…Increases in mean cell chiasma frequency generally result in chiasmata being formed in these interstitial regions with concommitant breakup of supergene complexes normally inherited as units. Again this situation is similar to that described in Lolium and Festuca by Rees and Dale (1974), in wheat by Zarchi et a!., (1972Zarchi et a!., ( , 1974 and in rye by Jones (1974).…”
Section: Resultssupporting
confidence: 71%
“…Two A-genome chromosomes carrying Spelt 52 blocks also have Spelt 1 blocks (arrows), indicating A t -G translocation. Species-specific translocation 6A t /1G revealed by GISH is indicated by arrows ary Bs (Mendelson and Zohary 1972;Zarchi et al 1974;Cebria et al 1994;Puertas 2002;Jones and Houben 2003;Jones et al 2008a, b;Carchilan et al 2009;Belyayev et al 2010). We detected one to seven B-chromosomes in different populations of Ae.…”
Section: Discussionmentioning
confidence: 83%
“…In Triticum speltoides, Zarchi et al (1974) observed that terminal chiasmata are reduced and interstitial chiasmata are increased in B-carriers. According to these authors, either the Bs exercise direct genetic control on chiasma distribution, or else they change the time-table of meiosis in such a way that pairing and/or chiasma terminalization are not completed.…”
Section: Discussionmentioning
confidence: 96%